2006
DOI: 10.1111/j.1399-6576.2006.00988.x
|View full text |Cite
|
Sign up to set email alerts
|

Volatile anaesthetics depolarize neural mitochondria by inhibiton of the electron transport chain

Abstract: Isoflurane and sevoflurane may act as metabolic inhibitors by depolarizing pre-synaptic mitochondria through inhibition of the electron transport chain, although isoflurane seems to inhibit mitochondrial function more significantly than sevoflurane. Both agents inhibit the respiratory chain sufficiently to cause ATP synthase reversal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 50 publications
(60 reference statements)
1
35
0
Order By: Relevance
“…H 2 S is thought to specifically inhibit complex IV in the respiratory chain, whereas isoflurane has been shown to be more specific for complexes I and V (Hanley et al, 2002;Bains et al, 2006). It is possible that the different sites of inhibition within the complex array of interacting subunits might actually oppose each other's actions via allosteric communication.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…H 2 S is thought to specifically inhibit complex IV in the respiratory chain, whereas isoflurane has been shown to be more specific for complexes I and V (Hanley et al, 2002;Bains et al, 2006). It is possible that the different sites of inhibition within the complex array of interacting subunits might actually oppose each other's actions via allosteric communication.…”
mentioning
confidence: 99%
“…Halothane, isoflurane, and sevoflurane all inhibit complex I activity in cardiac mitochondria, whereas sevoflurane and isoflurane also inhibit complex V to some extent (Hanley et al, 2002;Bains et al, 2006). Volatile anesthetics bind specifically to many mitochondrial proteins and preferentially accumulate in mitochondria (Eckenhoff and Shuman, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Anesthetic-induced inhibition of mitochondrial electron transport could lead to increased O 2 -levels and downstream reactions, which could trigger APC [9]. Moreover, isoflurane and sevoflurane both inhibit mitochondrial electron transport [12], whereas N 2 O does not inhibit mitochondrial electron transport or ATP formation [13,14]. Many investigators have shown that protein kinase C (PKC), ATP-sensitive mitochondrial and sarcolemmal potassium (mitoK ATP ?…”
Section: Discussionmentioning
confidence: 99%
“…In pig heart studies, the volatile anesthetics halothane, isoflurane, and sevoflurane inhibit complex I activity (NADH:ubiquinone oxidoreductase) [Hanley et al, 2002]. In rat brain, the inhaled anesthetics isoflurane and sevoflurane inhibit complexes I, IV, and V as well as DC under different conditions [Bains et al, 2006]. These effects may not all be deleterious, as depolarization may prevent ischemic injury by activation of signaling pathways through mechanism previously described [Moe et al, 2004].…”
Section: Anesthetics As a Model Of Mitochondrial Toxicitymentioning
confidence: 96%